Dietary supplementation with plant extracts for amelioration of persistent myofascial discomfort in the cervical and back regions: a randomized double-blind controlled study - Pérez-Piñero, Silvia; Muñoz-Carrillo, Juan Carlos; Echepare-Taberna, Jon; Luque-Rubia, Antonio J.; Millán Rivero, Jose Eduardo; Muñoz-Cámara, Macarena; Díaz Silvente, María Josefa; Valero Merlos, Eloina; Ávila-Gandía, Vicente; Caturla, Nuria; Navarro, Pau; Cabrera, María; et al. (Frontiers in Nutrition, 2024)
Background: Back pain is a common health problem that affects both workers and older people, reducing their quality of life. The primary objective was to assess the effect of dietary supplementation with plant extracts of rosemary, ashwagandha, and sesame consumed for 12 weeks on the intensity of back pain.Methods: A single-center randomized double-blind study with three parallel arms depending on the product consumed. The duration of treatment was 12 weeks. The investigational product, Berelief ® , contained a blend of three polyphenolic standardized extracts: rosemary (Rosmarinus officinalis L.), ashwagandha (Withania somnifera L.), and sesame (Sesamum indicum L.) seed. Two doses were tested: low dose (400 mg) and high dose (800 mg). There were 42 subjects in the placebo group, 39 in the low dose and 42 in the high dose groups.